Wolna Partia Demokratyczna po zjednoczeniu Niemiec (1990-2013) - Kruk, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author's intent is to present the meaning of the Free Democratic Party on the political scene of reunited Germany, from 1990 until 2013. FDP's activity in government coalitions as well as the liberals' activity in opposition in years 1998-2005. The influence of FDP, measuerd in the percentage of votes received and the results In elections, was limited in 2013, when the party didn't reach the five percent threshold and remained outside of the parliament.
Keywords: Wolna Partia Demokratyczna; Freie Demokratische Partei (FDP); liberalizm; Niemcy; od 1989 r.